From Antz to Titanic : reinventing film analysis - Barker, Martin, 1946-; Austin, Thomas, 1966- (Pluto Press, 2000)
Rejecting much of the baggage that surrounds contemporary film analysis, the authors work back from the problems their students have encountered to literally strip the subject of film analysis down to its bare essentials.